Urban ministry in a new millennium - Claerbaut, David (Waynesboro, GA Authentic Media, 2005)
Contents : Urban ministry : Biblical mandate; The global city and the inner city; Urban stratification and the neighbourhood church; Poverty from and institutional perspective; Insecurity as a way of life; Youth; Minorities; Socialization into victim blaming; The urban church and the urban minister; New directions in urban ministry. Includes bibliographical references and index.
First edition published Grand Rapids, MI, Zondervan, 1983
Keywords: City churches; Church work in urban areas